IMPLEMENTASI METODE ABACAGA DALAM MENINGKATKAN PRESTASI BELAJAR MEMBACA PERMULAAN DI MI ROUDLOTUL JANNAH MALANG - Siti Asfirotul Khasanah; Rosichin Mansur; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is based on the implementation of the abacaga method in improving reading achievement in students' beginning reading at MI Roudlotul Jannah, in the classroom many students tend to make noise, are busy, do not pay attention to the teacher. This research was conducted at MI Roudlotul Jannah Malang. The purpose of this study is to describe the learning of beginning reading, the application of the abacaga method and the evaluation of the application of the abacaga method in improving the learning achievement of beginning reading in MI Roudlotul Jannah Malang. This type of research uses a qualitative approach to the type of case stud. Data collection uses documentation, interviews, observations. Data analysis uses data reduction, data presentation and drawing conclusions. The results of this study are in the beginning of learning to read in thematic learning and supported by a s`pecial program that is the abacaga method and evaluation is carried out in terms of the process and results